KAJIAN PENGANGKUTAN PERSAMPAHAN DI KOTA SEMARANG BERDASARKAN GRAFIK PENGENDALI KECEPATAN - Maryono, Maryono; Wahyudi, Bramanthyo Heru (Universitas Diponegoro, 2007)
Some issues arouse an opinion that the activity of garbage transportation systems in Semarang aren’t work properly. This transportation systems management in Semarang are able to be evaluated from aspect of time-limited transportation systems that which determines the efficient routes, so that it could be solve the issues of garbage transportation systems based on the minimum time-limit (not always the route with the nearest distances) from the dump-truck to the direction of TPA. It found that the velocity of dump-truck is 28 km/hours above the minimum services standard, which is 25 km/hours. It also found that quality of the effective time of garbage transportation systems in Semarang is 1,026 or PKP ≈ 1, which depict that there is a lot of garbage that not well-distributes to the TPA in several zone. Whereas the efficient velocity of the dump-truck are about 26-28 km/hours. Overall we can conclude that the time-efficiency of garbage transportation systems in Semarang is in a middle conditions.